Auxiliary Teaching and Student Evaluation Methods Based on Facial Expression Recognition in Medical Education - Xueling Zhu; Roben A Juanatas (JMIR Human Factors)
AbstractTraditional medical education encounters several challenges. The introduction of advanced facial expression recognition technology offers a new approach to address these issues. The aim of the study is to propose a medical education–assisted teaching and student evaluation method based on facial expression recognition technology. This method consists of 4 key steps. In data collection, multiangle high-definition cameras record students’ facial expressions to ensure data comprehensiveness and accuracy. Facial expression recognition uses computer vision and deep learning algorithms to identify students’ emotional states. The result analysis stage organizes and statistically analyzes the recognized emotional data to provide teachers with students’ learning status feedback. In the teaching feedback stage, teaching strategies are adjusted according to the analysis results. Although this method faces challenges such as technical accuracy, device dependency, and privacy protection, it has the potential to improve teaching effectiveness, optimize personalized learning, and promote teacher-student interaction. The application prospects of this method in medical education are broad, and it is expected to significantly enhance teaching quality and students’ learning experience.